Rhamnolipid Enhances the Nitrogen Fixation Activity of Azotobacter chroococcum by Influencing Lysine Succinylation - Li, Jin; Pan, Hu; Yang, Hui; Wang, Chong; Liu, Huhu; Zhou, Hui; Li, Peiwang; Li, Changzhu; Lu, Xiangyang; Tian, Yun (Frontiers in Microbiology, 2021)
The enhancement of nitrogen fixation activity of diazotrophs is essential for safe crop production. Lysine succinylation (KSuc) is widely present in eukaryotes and prokaryotes and regulates various biological process. However, knowledge of the extent of KSuc in nitrogen fixation of Azotobacter chroococcum is scarce. In this study, we found that 250 mg/L of rhamnolipid (RL) significantly increased the nitrogen fixation activity of A. chroococcum by 39%, as compared with the control. qRT-PCR confirmed that RL could remarkably increase the transcript levels of nifA and nifHDK genes. In addition, a global KSuc of A. chroococcum was profiled using 4D-label-free quantitative proteomic approach. In total, 5,008 KSuc sites were identified on 1,376 succinylated proteins. Bioinformatics analysis showed that the addition of RL influence on the KSuc level and the succinylated proteins were involved in various metabolic process, particularly enriched in oxidative phosphorylation, TCA cycle, and nitrogen metabolism. Meanwhile, multiple succinylation sites on MoFe protein (NifDK) may be influenced nitrogenase activity. These results would provide an experimental basis for the regulation of biological nitrogen fixation with KSuc, and shed new light on the mechanistic study of nitrogen fixation.